PENGETAHUAN, KUALITAS HIDUP DAN BIAYA SAKIT PASIEN DENGUE DI RS PKU MUHAMMADIYAH GAMPING - Supadmi, Woro; Elvinda, Esty; Aryani Perwitasari, Dyah; Noor Faridah, Imaniar (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
The incidence of dengue virus infection in the D.I. Yogyakarta reached 3,618 cases in 2020. Based on its clinical manifestations, dengue virus infection is divided into Dengue Fever (DF), Dengue Haemorrhagic Fever (DHF), and Dengue Shock Syndrome (DSS). This study aims to identify the level of knowledge, quality of life, and costs of dengue patients at PKU Muhammadiyah Gamping Hospital from March 2021 to October 2021. This study used a cross-sectional design. The measurement of the patient's knowledge level used a questionnaire knowledge of dengue, while the quality of life was assessed using EQ-5D-5L for adult patients and EQ-5D-Y for pediatric patients. The cost of illness data from the hospital finance database. This study involved 31 respondents with the characteristics aged 16-40 years (54.84%), male (87.1%), using BPJS insurance (80.65%), and an average length of stay of 4 days (51.61%). The patient's level of knowledge about dengue, knowledge of dengue prevention, and dengue prevention behavior reached 74.20% (sufficient), 74.20% (sufficient), and 77.42% (sufficient) respectively. The quality of life of dengue patients reached 100% and 85.2% in DF patients, while the DHF patients felt a few anxious/depressed (sad). The average cost of illness in DF patients was Rp. 2,796,386 and Rp. 3,378,537 in DHF patients.